CRISIS MANAGEMENT IN EDUCATION - CHALLENGES AND STRATEGIES FOR SCHOOL LEADERS IN TURBULENT TIMES - Sofy AMNONY; Nicolae BIBU; Maria-Madela ABRUDAN (Annals of the University of Oradea: Economic Science)
This study synthesize the critical role of crisis management in educational settings, focusing on the challenges faced by school leaders during unprecedented crises such as the COVID-19 pandemic and violent conflicts. Through a systematic review of recent literature (2020-2023) and synthesis of empirical findings, this research explores key concepts in crisis management, identifies major challenges, and discusses effective strategies for school principals to navigate these turbulent times. The study employs a theoretical framework based on organizational resilience and adaptive leadership to analyze the complexities of educational crisis management. Findings highlight the importance of adaptability, emotional support, technological integration, and professional development in maintaining educational continuity and fostering resilience within school communities. Implications for educational policy, leadership training, and future research directions are discussed.